(untitled) (Diametros, 2024)
The article discusses off-label use of medicinal products and problems in separating situations in which this form of treatment constitutes innovative therapy from normal medical practice. It highlights the important risk of qualifying routine therapy as a medical experiment and the relationship between the notion of “current medical knowledge” and the Summary of Product Characteristics. The effectiveness in determining whether the proposed method of treatment is a new or used method is discussed, and the postulate of the medical activity of the scientific society in this regard is given. Finally, the implications of considering off-label treatment as a therapeutic experiment, including the need to obtain the opinion of a bioethics committee and to subscribe for the third party liability insurance, as well as their impact on patient safety, legal security of the doctor and overall accessibility of medical treatment are presented.